2004
DOI: 10.1111/j.1365-2133.2004.06065.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of dermatologists', surgeons' and general practitioners' surgical management of cutaneous melanoma

Abstract: This study showed that dermatologists manage an increasing majority of melanoma patients and that there were significant differences in the surgical treatment of melanoma between dermatologists and surgeons. Survival was significantly better in the dermatology-treated group, suggesting that dermatologists should have a central role in melanoma management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(57 citation statements)
references
References 18 publications
5
49
0
3
Order By: Relevance
“…Further, GP melanomas were more frequently of nodular type, which is a significant finding, in line with a previous study [14]. Nodular melanomas have a vertical rather growth pattern than the primarily horizontal growth pattern of superficial spreading melanomas.…”
Section: Discussionsupporting
confidence: 78%
“…Further, GP melanomas were more frequently of nodular type, which is a significant finding, in line with a previous study [14]. Nodular melanomas have a vertical rather growth pattern than the primarily horizontal growth pattern of superficial spreading melanomas.…”
Section: Discussionsupporting
confidence: 78%
“…5,[8][9][10] On the other hand, studies employing larger series and where the risk of bias has been minimised by blinding the location of excision biopsy during quality rating, have found no significant difference. 6,12,13 Previous research has explored the relationship between who excises melanoma 1998. 25 The authors compared survival by the training background (dermatologist, plastic surgeon, or general surgeon) of the operators who had removed at least In this study, differences in survival between the GP-and the dermatologytreated groups were non-significant and the authors concluded that this was because the GP group was small and because most GPs performing skin surgery in the study area did so in close cooperation with the local dermatology department.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…6,11,12 To date, there have been relatively few studies that compare outcomes for patients with melanoma treated initially by different specialties; however, one study has suggested that dermatologists may achieve the best results. 13 Notably, however, in Australia, which has among the highest global incidence of cutaneous melanoma, most melanomas are biopsied initially by GPs in primary care, without compromising survival compared with the UK.…”
Section: Introductionmentioning
confidence: 99%
“…Eight guidelines do not specify which doctor should perform follow-up and ten recommend follow-up by a melanoma specialist, thereby reflecting the absence of evidence for the 'best follow-up doctor'. Only one retrospective study advocates a central role for dermatologists in a multidisciplinary melanoma management team, because of improved survival compared with surgeon's patients [63]. Unfortunately, follow-up surveillance was not discussed and patient characteristics in the dermatology group were more favorable, so the value of this study is limited.…”
Section: Who Should Perform Follow-up?mentioning
confidence: 91%